DEVELOPING DIGITAL RUBRICS OF SIX TASKS OF KKNI IR 4.0-BASED FOR TEFL SUBJECT - Dewi, Nora Ronita; Siregar, Masitowarni; Saragih, Anggraini Thesisia (Association of Language Teachers in Southeast Asia (ALTSA), 2020)
This study is aimed at developing rubrics of six tasks of Teaching English as a Foreign Language (TEFL) the subject of the KKNI Industrial Revolution 4.0-based of an English Education Study Program at UNIMED. The objectives of this research are to analyze the rubrics of TEFL subject used at the 3rd semester of English Education Study Program and develop the appropriate KKNI rubrics based on the students? needs. This study is mainly focused on developing Critical Book Report, Critical Journal Report, Engineering Ideas, Mini Research, and Projects rubrics. Research and Development applied in this research and the results show that the rubrics used in the 3rd semester at English Education Study Program is developed through implementing the simplification of R&D. The rubrics indicated low competency for the students after analyzing the questionnaires given. New rubrics are designed to answer the needs of the students. Generally, the existing TEFL rubrics are less relevant for the needs of 3rd semester students. In terms of descriptor rubrics, they are not suitable with the needs of the Lesson Plan and the tasks of TEFL rubrics needed by the students are irrelevant for their needs where the topics or contents used in the course book are useful in the learning outcome of this subject.